Changes in volatile and non-volatile compounds of model kimchi through fermentation by lactic acid bacteria. (May 2019) - Choi, Yun-Jeong; Yong, Sojin; Lee, Min Jung; Park, Sung Jin; Yun, Ye-Rang; Park, Sung-Hee; Lee, Mi-Ai
Abstract: We analyzed the quality characteristics of model kimchi fermented with lactic acid bacteria (LAB; Leuconostoc mesenteroides, Leuconostoc citreum, Lactobacillus plantarum, Lactobacillus sakei, Weissella cibaria, and Weissella koreensis ). The model kimchi was heat-treated at 60 °C for 10 min and then inoculated with different LAB strains. The fermentation process was performed at 15 °C for 48 h. Volatile and non-volatile flavour compounds, cell growth, pH, and sensory properties were monitored during fermentation. The pH decreased rapidly in kimchi fermented with L. mesenteroides, L. citreum, and L. plantarum along with high sugar utilization and acid production. The flavour profile of model kimchi varied with different LAB starter cultures. The sensory preference was higher when acetic acid and lactic acid were produced at the same time. There are significant positive correlations between overall preference and acetic acid (0.880), mannitol (0.871), and diallyl sulfide (0.863) concentrations. Principle component analysis (PCA) score plots showed clear differences in the metabolites of kimchi according to the LAB starter culture used in fermentation. Therefore, the type and concentration of metabolites present in kimchi are greatly affected by strain of LAB and fermentation time. Highlights: The fermentation process of model kimchi was carried out at 15 °C for 48 h. Volatile and non-volatile compounds produced by Kimchi fermentation were measured. Kimchi flavour characteristics were associated with lactic acid bacteria starter cultures. Kimchi preference correlated with acetic acid, mannitol, and diallyl sulfide levels. Metabolite production was affected by the lactic acid bacteria strains.